Illuminate : ignite change through speeches, stories, ceremonies, and symbols - Duarte, Nancy; Sanchez, Patti (New York, New York : Portfolio/Penguin, 2016)
'Illuminate' demonstrates how, though the power of persuasive communication, one can turn an idea into a movement, as compared with the likes of Steve Jobs, Dr. Martin Luther King, Jr., Starbucks, IBM, and more.
Leaders move others forward -- Listen empathetically to light the path. Case study : IBM and market basket -- The torchbearer's toolkit. Case study : Starbucks -- Moment of inspiration. Case study : Interface -- Moment of decision. Case study : Rackspace -- Moment of bravery. Case study : civil rights -- Moment of endurance. Case study : charity: water -- Moment of reflection. Case study : Chick-fil-A -- Moment of disruption. Case study : Apple -- Confessions of a torchbearer. Case study : Duarte, Inc. -- The journey begins again.
Includes bibliographical references and index.
Keywords: Organizational change -- Management; Communication in management; Leadership